Association of Helicobacter Pylori Infection in Patients Having Coronary Artery Disease - Ranjit, A; Pathak, CM; Khanduja, K.L.; Ball, H.K.; Bhasin, D.K. (Nepalese Heart Journal, 2004)
Helicobacter pylori usually cause a lifelong infection of gastric mucosa that may lead to gastric ulcer and later on gastric cancer. H, pylori infection and coronary heart disease are common conditions in late middle and old age. Recently, some studies have found casual association between H. Pylori infection and coronary artery disease, cerebrovascular disease and atherosclerosis. The study was done to detect the presence of H. Pylori in patients of coronary artery disease (CAD) by 14C-urea breath test and to find out any possible association between H. Pylori infection and coronary artery disease,